Successful School Principalship: A Meta-Synthesis of 20 Years of International Case Studies - Jingping Sun; Christopher Day; Rong Zhang; Huaiyue Zhang; Ting Huang; Junqi Lin (MDPI AG, 2024)
This meta-synthesis crosses international borders by analyzing successful principalship across nine countries. With careful, detailed, systematic, and analytic synthesis, it critically explores research-informed understandings of successful principal leadership over the last 20 years. The paper is an interim report of reviews of the 85 articles and 23 chapters produced by the International Successful School Principal Project (ISSPP), the largest, longest-running international research project in this field. In that project, success is defined as the principal's ability to grow and sustain students' academic, personal, and social developments and achievements over time. The results add to existing knowledge of how successful school principals achieve success by examining high-quality, published case study evidence from Australia, Cyprus, Israel, New Zealand, Norway, Sweden, Spain, the UK, and the US. Results suggest common sets of core values, qualities, and practices among school principals, regardless of national contexts, conditions, or cultures. Because the research design is multi-perspective and multi-layered, the case studies also show significant, context-informed differences in timing, pace, and extent of application of improvement strategies. Thus, the findings of this synthesis paint a thorough and cohesive picture of who successful principals are and what they do over time at the global level to achieve success, as they navigate values-led school success in different contexts and improvement phases within complex internal and external ecological chrono-, macro-, exo-, meso-, and microsystems.